Debt and financial performance of REITs in Malaysia : a moderating effect of financial flexibility - Zalina Zainudin; Hafezali Iqbal Hussain; Izani Ibrahim; Rasidah Mohd Said (Penerbit Universiti Kebangsaan Malaysia, 2017)
The use of debt by REITs entity seems to be a puzzle in numerous REITs literature, as REITs are tax-exempted business entities. The trade-off theory implies that the financing strategy of using debt provides no value in a REIT entity with a marginal tax rate of zero. However, high dividend pay-out requirement has limit REITs’ ability to retain its internal earnings, thus require REITs to use debt to undertake its growth strategies. This study aims to investigate the great curiosity about the debt financing decision of REITs in Malaysia (MREITs) at all given no tax shield benefit and to examine the moderating effect of financial flexibility in a relationship between debt financing and the financial performance. Using the unbalanced panel data from all MREITs for the time period between 2005 and 2014, the results of this study are consistent with the pecking order theory in explaining the MREITs debt financing decision but are less supportive of the trade-off theory on tax benefits and agency theory of free cash flow on disciplinary tools. This suggests that MREITs use debt to support the growth needs than tax motives and the high dividend pay-out requirement behaves as a “disciplinary tool,” not through the use of debt. The findings also reveal that financial flexibility plays an important role to alter the negative relationship between debt financing and financial performance to positive relationship. This study serves as a useful guide for MREITs’ managers in managing financial flexibility as it has important moderating effects on the relationship between debt financing and financial performance.